1 Answer | Add Yours
`f(x) = e^x + root(3)(x)`
Let F(x) be the anti derivative of f(x).
To determine F(x), take the integral of f(x).
`F(x) = int f(x) dx = int (e^x + root(3)(x) ) dx = int e^xdx + int root(3)(x)dx`
To integrate the first term, apply the exponential formula `int e^u du = e^u + C` .
`= e^x + C + int root(3)(x) dx`
For the second term, express the radical as exponent. Then ,apply the power formula of integral which is `int u^n du = u^(n+1)/(n+1) + C ` .
`= e^x + C + int x^(1/3)dx`
`= e^x + C + x^ (4/3) /(4/3) + C`
`= e^x + C + (3x^(4/3))/ 4 + C`
Since C represents any number, we may re-write C + C as C only.
`= e^x + (3x^(4/3))/4 + C`
Hence, the anti derivative of `f(x) = e^x + roo(3)(x)` is `F(x)=e^x + (3x^(4/3))/4 + C` .
We’ve answered 288,358 questions. We can answer yours, too.Ask a question